PENGARUH INFLASI DAN SUKU BUNGA TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PERBANKAN - Jelita, Jelita; Nurfadilah, Mursidah; Jamal, Sri Wahyuni (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2025)
This study analyzes the effect of inflation and interest rates on banking sector stock prices. The objective is to determine the partial and simultaneous effects, helping investors understand macroeconomic factors in investment decisions. A quantitative approach was used with multiple linear regression. A sample of 14 banking companies was selected using purposive sampling techniques, and secondary data from 2020–2024 from the Indonesia Stock Exchange (IDX) and Bank Indonesia was used. Inflation did not have a significant effect on stock prices. Conversely, interest rates showed a significant partial effect. Simultaneously, inflation and interest rates jointly influence banking sector stock prices. Inflation does not significantly affect banking stock prices, while interest rates have a significant effect. Investors are advised to pay attention to interest rates, and further research should include additional macroeconomic variables